Use of Cetaceans as Bait in Southern Bahia, Brazil, by Expert Fishermen that Market Shark Fins: A Lucrative Trade and Two Threatened Zoological Groups - Barbosa-Filho, Marcio Luiz Vargas; Fonseca Barreto, Rebeca Mascarenhas; Siciliano, Salvatore; Seminara, Cecilia Inés; Costa-Neto, Eraldo Medeiros (Ethnobiology Letters, 2018)
In Brazil, despite the existence of a federal law prohibiting the capture and harassment of marine mammals, the use of fat as fishing bait has been reported. However, the processes of obtaining and using bait have not been described for southern Bahia state. The objective of this study was to learn how these processes occur in populations of fishermen along the southern coast of the state and how to minimize the negative impacts on the cetacean population. Semi-structured interviews about shark fishing and use of cetaceans as bait were conducted with 65 shark fishers from Ilhéus, Una, and Canavieiras municipalities in Brazil. Data were analyzed using descriptive statistics with percentage distributions. Fishermen emphasized the adipose tissue of dolphins, whales, and porpoises as preferred bait for catching sharks. Of our sample, 81.5% of fishers knew about the use of fat as bait and 56.9% knew someone who had caught cetaceans. Regarding beached whales, 67.7% reported knowing of their use and 20% had used them. This study shows the interrelation of people’s use of two zoological groups: cetaceans as bait, which represents a threat to the group, and sharks for commercialization, a group in which 75% of species are endangered. It shows the ecological impacts of these interactions. Protection measures will only be effective when they approach the local culture in an integrated manner by considering traditional customs that have developed from centuries of exploitation.